Polymerase chain reaction for antigen receptor rearrangement: Benchmarking performance of a lymphoid clonality assay in diverse canine sample types - E. J. Ehrhart; Shukmei Wong; Keith Richter; Victoria Zismann; Carolyn Grimes; William Hendricks; Chand Khanna (Journal of Veterinary Internal Medicine, 2019)
Abstract Background Polymerase chain reaction for antigen receptor rearrangement (PARR) is a molecular diagnostic tool used for discrimination of lymphoid malignancies in dogs from benign processes. Assay variations have been described and are commercially available, but performance metrics are not uniformly reported. Objectives To describe performance (accuracy, sensitivity, specificity) and rigorous benchmarking of a PARR protocol (ePARR) in clinically relevant samples. Animals One hundred eighty‐one client‐owned dogs. Methods Lymphoma and benign tissues representative of the clinical spectrum with gold standard histopathologic and immunohistochemical diagnoses were collected. Assay development and benchmarking were performed on fresh frozen (FF) tissue, formalin‐fixed paraffin‐embedded (FFPE) tissue, flow cytometry pellets, and air‐dried fine‐needle aspirates (FNA). Assay performance was determined for FFPE from 56 dogs (18 B‐cell lymphoma, 24 T‐cell lymphoma, and 14 non‐lymphoma), 80 frozen flow cytometry pellets (66 B‐cell lymphoma, 14 T‐cell lymphoma, 0 non‐lymphoma), and 41 air‐dried FNA slides (23 lymphoma, 18 non‐lymphoma). Results For discrimination of lymphoma versus non‐lymphoma, ePARR had 92% and 92% sensitivity and specificity on FFPE with 92% accuracy, 85% sensitivity from flow cytometry pellets (non‐lymphoma was not evaluated to calculate specificity) with 85% accuracy, and 100% and 100% sensitivity and specificity for FNA with 100% accuracy. Stringent quality control criteria decreased assay success rate without significant performance improvement. Performance metrics were lower in most cases for discrimination of B‐ or T‐cell versus non‐B‐ or non‐T‐cell samples than for lymphoma versus non‐lymphoma. Conclusions and Clinical Importance These benchmarking data facilitate effective interpretation and application of PARR assays in multiple sample types.